Zerebrale Durchblutung in Ruhe und nach CO2-Stimulation bei Patienten mit einseitiger Karotisobstruktion - Chatzipanagiotou, Th.; Müller-Brand, J.; Radü, E. W.; Rem, J.; Fridrich, R. (Nuklearmedizin - NuclearMedicine, 1988)
Using the 16-detector 133Xe-NaCI-technique (Novo Cerebrograph) quantitative measurements of regional cerebral blood flow (rCBF) were performed in 14 patients with unilateral carotis obstruction before and during stimulation with 3% CO2 inhalation. In all patients resting studies did not show any significant differences in hemispheric perfusion. In 11 patients the hemispheric blood flow increased significantly (by more than 6%) during CO2 inhalation on the side without carotis obstruction. The following results were found after 3% CO2-stimulation over the hemisphere with the obstructed carotid artery: 1) rCBF increased significantly on both sides (n = 6) indicating the sufficiency of cerebral collateral circulation; 2) a side-to-side significant difference (n = 4) with the lower perfusion on the pathological side, indicating a decreased or suspended reserve capacity; and 3) bilateral loss of cerebrovascular reactivity (n = 4) as indicator of insufficiency of cerebral collateral circulation. Asymmetry in rCBF or missing cerebrovascular reserve are indications for surgical treatment of the carotis obstruction.